Current recruitment issues in the Singapore marine industry - Gan, Kian Keong (2014)
The marine industry is an important part of the Singapore economy, evident by its past and present contributions to the Republic’s economic growth. One of the major threats confronting this labour-intensive industry is the shortage of semi-skilled and skilled operative workers in the local labour market. This project was, therefore, initiated to explore the current recruitment issues in the marine industry, in the light of this prevailing labour shortage situation. More specifically, this study aimed to understand the recruitment practices and problems of marine companies in their recruitment of operative workers.